A study on traditional and modern courtship practices, attitudes, and patterns in Tacloban City, Leyte. - Balondo, Eunice D. (Tacloban City Eunice D. Balondo, 2009)
This study aims to uncover the traditional and modern courtship practices, attitudes and patterns in the city of Tacloban, Leyte. A descriptive study of both and a comparative study on traditional and modern courtship was made along with insights on gender roles and issues involved in this social transaction.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social Science